Retroplacental hematoma associated to tubo ovarian abscess in 23 weeks of pregnancy. A case report. - Neysi Chávez Rodríguez; Yobadys del Sol Hernández; Mariam Zam; Belkis Pérez Hernández; Práxedes Rojas Quintana; Alberto Jorge Fernández (Medisur)
A 30 year-old female patient with 23 weeks of pregnancy and with asthma antecedent is presented. She had treatment with bronchodilators. She came to the provincial medical emergency centre due to an intense pain with a sudden appearance in the lower abdomen, vomiting, shortness of breath, and sweating. The presence of a retroplacental hematoma caused due to a tubo-ovarian abscess associated to an abdominal peritonitis was corroborated. The way in which the disease was manifested and evolved is described.